100 - SOMATOTYPE CHARACTERISTICS AND THE CORPORAL DENSITY OF THE STUDENTS OF THE CENTER OF GRADUATION OF OFFICERS OF NAVAL SCHOOL. A COMPARATIVE STUDY AMONG THE YEARS OF GRADUATION. (Fiep Bulletin - online, 2011)
The main goal of this study it was to identify the somatotype profile of the corporal density of the naval school candidates during the years of formation. The population of the candidates is 821. The first sample has 82 candidates, male gender, random selected, being, 24 from 1st grade, 21 from 2nd grade, 20 from 3rd grade and 17 from 4th grade ( about 10%/ year), range ages between 18 and 25 years old, median of 21,37 +- 1,41. Was collected information about age, weight, height, cutaneous folds, perimeters and diameters. For the somatotype calculation was used the heath and Carter (1990), anthropometry method. To calculate the fat percentual (%G), it used the Jackson and Pollock protocol (1993), three folds, correlated to Siri equation (1961). The measure was obtained from the right side, according ISAK of Norton and Olds (2000) recommendations. The statistical treatment was through descriptive analyzes, according to the Costa Neto (1995), with the main purpose was to obtain the profile of the data set, through measure of localization (medium) and dispersion (shunting line- standard) . It admitted the level of significance of p
Keywords: Obesity; Anthropometry; Health Profile; Body Composition